Nanoscale modulation of electronic states across unit cell steps on the surface of an epitaxial colossal magnetoresistance manganite film - Rana, Abhimanyu; Bogle, Kashinath A.; Game, Onkar S.; Patil, Shankar; Valanoor, Nagarajan; Ogale, Satishchandra B. (Applied Physics Letters, 2010)
The nature of electronic states near the edge of unit cell steps on the surface of epitaxial La(0.7)Sr(0.3)MnO(3) (LSMO) thin films grown by real-time reflection high energy electron diffraction monitored pulsed laser deposition is examined by scanning tunneling microscopy and scanning tunneling spectroscopy techniques. It is observed that the electronic states are strongly modulated near the step edge with considerably high gap at the edge and low gap on the terrace. This modulation weakens at low temperature. The temperature evolution of the density of states and the nature of gap in deep metallic state of LSMO are also discussed. (C) 2010 American Institute of Physics. [doi:10.1063/1.3455886]
Keywords: colossal magnetoresistance; electronic density of states; lanthanum compounds; magnetic epitaxial layers; Nanostructured materials; pulsed laser deposition; reflection high energy electron diffraction; scanning tunnelling microscopy; scanning tunnelling spectroscopy; strontium compounds

Strong electric field modulation of transport in PVDF/MWCNT nanocomposite near the percolation threshold - Chanmal, Chetan; Deo, Meenal S.; Rana, Abhimanyu; Jog, Jyoti Prakash; Ogale, Satishchandra B. (Solid State Communications, 2011)
A nanocomposite comprising of multiwalled carbon nanotubes (MWCNT) embedded in ferroelectric Poly(vinylidene fluoride) PVDF polymer matrix is examined for electric field induced transport modulation. The pulsed laser deposition (PLD) grown thin films of the nanocomposite with different MWCNT content were characterized. When used as a channel layer in a field effect transistor configuration, a strong electric field modulation of the transport was realized just below the percolation threshold. We believe that this nanocomposite non-percolating channel concept can provide several opportunities for FET devices for organic electronics. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Field effect device; pulsed laser deposition; PVDF; Scanning tunneling microscopy